The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.11114/jets.v7i8.4053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Two Dialogical Feedback Methods for Improving Pre-Service Teacher's Perceived Confidence and Competence to Teach Physical Education Within Authentic Learning Environments

Abstract: This novel study investigates the effectiveness of two dialogical feedback methods, peer dialogue assessment and dialogical feedback provided by an academic, when they are used as assessment as learning tools in undergraduate physical education courses. Education students from the University of Newcastle, Australia (n=288), participated in this investigation and completed eight weeks of face-to-face on-campus physical education studies followed by a 3 or 4 week in-school teaching program (~1.5 hrs/week). Stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…This collaborative approach involves coaches in the feedback process to maximise learning and development 41,65. It also extends current practices in educational contexts such as: professional learning communities research,66 instructional ‘rounds’,34 and peer-dialogue in higher educational settings 65,67. Following the coach assessment and reflection session, coaches continued implementing MASTER strategies in their normal training sessions and were required to undertake two peer observations of a colleague (using the MASTER observation checklist).…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…This collaborative approach involves coaches in the feedback process to maximise learning and development 41,65. It also extends current practices in educational contexts such as: professional learning communities research,66 instructional ‘rounds’,34 and peer-dialogue in higher educational settings 65,67. Following the coach assessment and reflection session, coaches continued implementing MASTER strategies in their normal training sessions and were required to undertake two peer observations of a colleague (using the MASTER observation checklist).…”
Section: Methodsmentioning
confidence: 87%
“…Following the coach assessment and reflection session, coaches continued implementing MASTER strategies in their normal training sessions and were required to undertake two peer observations of a colleague (using the MASTER observation checklist). Feedback and professional dialogue between the coach and the peer observer followed the peer observation sessions as this has shown to be an effective and well-received learning strategy for use in the context of delivering sport and physical education sessions 41,65,67. To facilitate open discussion, coach peer-evaluation discussions were not recorded or analysed in this study; however, this may be a useful process to show potential growth or development over the intervention phase in future studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study participants communicated information that supports the findings within the extant literature. Extensive research has indicated that constant, constructive feedback delivered formally and informally has a positive impact on teachers’ self-efficacy and allows them to make progress in their teaching performance (Akkuzu, 2014; Eather et al, 2019; Memduhoğlu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To do so, it is essential to pay attention to the pedagogy of dialogue, actively following up on the future teachers in their first contacts with the classroom. This will allow them to achieve confidence and competence in themselves to create their own professional identity (Eather et al, 2019).…”
Section: Discussionmentioning
confidence: 99%